PELATIHAN KEPEMIMPINAN DAN MANAJEMEN TIM PADA SISWA SMK MUHAMMADIYAH 3 TANGERANG SELATAN: LEADERSHIP AND TEAM MANAGEMENT TRAINING FOR STUDENTS OF MUHAMMADIYAH 3 VOCATIONAL SCHOOL IN SOUTH TANGERANG - farida, syarifah ida (Jurnal Dedikasi Matematika & Sains, 2025)
This community service activity aims to provide training and outreach to produce a generation of excellent human resources. The methods used in this activity include training and motivational encouragement delivered in the form of lectures and face-to-face audiences. The target of this activity is the students of Muhammadiyah 3 Vocational School In South Tangerang, located at Jl. Dewi Sartika Jl. Nangka No.3, Ciputat, Subdistrict Ciputat, South Tangerang City, Banten 15411. The results show that after the implementation of this activity for the students: 1) Improve leadership and team management skills. 2) Increase self-confidence and communication abilities. 3) Prepare themselves to face challenges in the workforce or organizations. For the school: 1) Improve the quality of graduates ready to compete in the job market. 2) Building the image of the school as an institution that cares about the development of students’ soft skills. 3) For the Community: 1) Creating a young generation capable of actively contributing to social activities and community organizations. 2) Encouraging the emergence of young leaders who are integral and responsible.